Do preventative care guidelines emphasize behaviour change? A content analysis of three commonly used Australian general practice guidelines. Issue 2 (8th November 2022) - Prathivadi, Pallavi; Advocat, Jenny; Ball, Lauren; Clark, Alex; Williams, Lauren T.; Sturgiss, Elizabeth
Abstract: Rationale: Preventive health is a core part of primary care clinical practice and it is critical for both disease prevention and reducing the consequences of chronic disease. In primary care, the 5As framework is often used to guide behaviour change consultations for smoking, nutrition, alcohol use and physical activity. Aims and Objectives: Our objective was to analyze the emphasis placed on each 5As term in commonly used guidelines in Australian general practice and compare this to behaviour change terms/concepts essential to effective consultations. Method: A content analysis was undertaken to explore frequency of 5A terms and key behaviour change concepts/terms chapter‐by‐chapter across the three most commonly used guidelines in Australian general practice. Results: The prevalence of each 5As term differed in all three guidelines, with 'Arrange' being mentioned the least often. Behaviour change concepts and terms, such as patient‐centredness, listening, trust and tailoring, were infrequently used and were often confined to a separate chapter of the guidelines. Conclusion: The language and content of the guidelines contrast with known effective components of behaviour change consultations. Future revisions could reconsider emphasis of 5As terms to avoid paternalistic approaches, improve shared language across guidelines and incorporate behavioural science principles to enhance preventative care delivery.